Optimization Ship Maneuvers During Bad Weather When Crossing Shipping Lanes Narrow Channel of Barito River at SPB. LAIS - Saputra , Fiagiv Ferdinan; Wibowo, Wahju; Nurhidayati, Indah (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
This study aims to explore how to optimize ship maneuvers when traversing the Barito River's small shipping channel in bad weather. Researchers have observed that when a ship turns through a bend in the narrow Barito River channel, particularly in inclement weather, there are frequently hazards or undesirable things that occur. This is because the duty chief on board failed to pay attention to the direction and strength of the current, which caused the ship's stern to be carried away by the current, closing the channel. This study's qualitative descriptive methodology is based on facts experienced by the researchers on board and generates data directly from the research location. Direct interviews with research participants, literature and documentation studies, and observation are the methods used in this instance to get data about the object. According to the findings of this study, ship movements during inclement weather while traversing the Barito River's tight channel at SPB. LAIS. Manoeuvring errors resulting from the duty chief's carelessness are the primary reason of the ship's difficulties. In order to ensure that the voyage proceeds safely, effectively, and efficiently, the researcher recommends that the duty chief be more cautious while on duty and learn the proper technique for crossing the Barito River to prevent navigation dangers.